Beetles (Coleoptera) of Peru: A Survey of Families. Mycetophagidae Leach 1815 - Shepard, William D. (2020)
The diversity of the family Mycetophagidae (Coleoptera) is summarized for Peru. Two genera are recorded (Litargus Erichson and Thrimolus Casey). Comments are given on classification and distribution of the family, as well as known biology and natural history.